Ketunggalan Titik Tetap di Ruang Dislocated Quasi B-Metrik pada Pemetaan Siklik - malahayati malahayati (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2017)
The quasi b-metric dislocated space (dqb-metric space) was first introduced by Klin-eam and Suanoom in 2015. They had been proven the uniqueness of the fixed point in the dqb-metric space on cyclic mapping that provides the cyclic Banach contraction conditions. Furthermore, in 2016 Dolicanin et al showed that the fixed point singularity properties in the dqb-metric space can be proven without requiring the mapping to satisfy the cyclic metrics Banach contraction conditions. Both statements are proved equivalent in this paper.